2010
DOI: 10.1002/prot.22852
|View full text |Cite
|
Sign up to set email alerts
|

Universality of protein reentrant condensation in solution induced by multivalent metal ions

Abstract: The effective interactions and phase behavior of protein solutions under strong electrostatic coupling conditions are difficult to understand due to the complex charge pattern and irregular geometry of protein surfaces. This distinguishes them from related systems such as DNA or conventional colloids. In this work, we discuss the question of universality of the reentrant condensation (RC) of proteins in solution induced by multivalent counterions, i.e., redissolution on adding further salts after phase separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
186
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(200 citation statements)
references
References 40 publications
(53 reference statements)
12
186
1
1
Order By: Relevance
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules.…”
Section: Resultssupporting
confidence: 91%
“…The above results correlate well with the reentrant condensation of HSA in the presence of yttrium reported in the litterature. 12,18,23 Indeed, the increase in YCl 3 concentration first causes a reduction of the absolute value of the net charge of HSA molecules, decreasing inter-particle repulsion and promoting inter-particle attraction, whereafter the net charge of the HSA molecules reverses and its absolute value increases, causing renewed repulsion.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that surface patchiness has an important effect on the phase diagram [11]. Also, binding of multivalent ions to the protein surface can give rise to non mean-field behaviors beyond DLVO, such as charge inversion, re-entrant condensation and liquid-liquid phase separation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%